Neoliberal Urbanism Redux?. (24th April 2013) - Peck, Jamie; Theodore, Nik; Brenner, Neil
Abstract Neoliberalization processes have been reshaping the landscapes of urban development for more than three decades, but their forms and consequences continue to evolve through an eclectic blend of failure and crisis, regulatory experimentation, and policy transfer across places, territories and scales. The proliferation of familiar neoliberal discourses and policy formulations in the aftermath of the 2007‐09 world financial crisis masks evidence of more deeply rooted transformations of policies, institutions and spaces that continue to combatively remake terrains of urban development. Accordingly, the critical intellectual project of deciphering the problematic of neoliberal urbanism must continue to evolve. This essay outlines some of the methodological and political challenges associated with (re)constructing a ′moving map′ of post‐crisis neoliberalization processes. We affirm a form of critical urban theory that adopts a restlessly antagonistic stance towards orthodox urban formations and their dominant ideologies, institutional arrangements and societal effects, tracking their endemic policy failures and crisis tendencies while at the same time demarcating potential terrains for heterodox, radical and/or insurgent theories and practices of emancipatory social change.